2013
DOI: 10.1186/1478-811x-11-59
|View full text |Cite
|
Sign up to set email alerts
|

Activation state-dependent interaction between Gαq subunits and the Fhit tumor suppressor

Abstract: BackgroundThe FHIT tumor suppressor gene is arguably the most commonly altered gene in cancer since it is inactivated in about 60% of human tumors. The Fhit protein is a member of the ubiquitous histidine triad proteins which hydrolyze dinucleoside polyphosphates such as Ap3A. Despite the fact that Fhit functions as a tumor suppressor, the pathway through which Fhit inhibits growth of cancer cells remains largely unknown. Phosphorylation by Src tyrosine kinases provides a linkage between Fhit and growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Encouragingly, the development of carcinogen induced tumors in these mice can be prevented by administration of Fhit-expressing viral vectors. Moreover, Fhit overexpression enhances the susceptibility of many types of cancer cells to exogenous inducers of apoptosis (Zuo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Encouragingly, the development of carcinogen induced tumors in these mice can be prevented by administration of Fhit-expressing viral vectors. Moreover, Fhit overexpression enhances the susceptibility of many types of cancer cells to exogenous inducers of apoptosis (Zuo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The GST-FHIT (fragile histidine triad protein) expression plasmid was kindly provided by Y.H. Wong, ( 48 ). The pBS5051 expression plasmid contains the Aph1 coding sequence PCR-amplified from plasmid p19 kindly provided by Plateau ( 49 ).…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type Fhit in pCMV-SPORT6 was purchased from Invitrogen (Carlsbad, CA). Gα 16/z chimeras were constructed by overlapping PCR which swapped the corresponding regions of Gα 16 with Gα z as described previously [ 15 ]. Cell culture and Lipofectamine PLUS reagents, and anti-Fhit antibody were purchased from Invitrogen (Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Fhit-interacting molecules include β-catenin [ 11 ], ferredoxin reductase [ 12 ], Src tyrosine kinase [ 13 ] and ubiquitin conjugating enzyme 9 [ 14 ]. More recently, we have demonstrated that Fhit can distinguish between inactive and active signal transducing Gα subunits of the G q family [ 15 ]. This finding is intriguing as it may link Fhit to Gα q -dependent signals that modulate a variety of cellular events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation